Absorptive capacity in higher education institutions: a systematization of literature - Ciotti, Rogério; Favretto, Jacir (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The search of organizations for external knowledge and the subsequent incorporation of this in their internal environment are determining factors to achieve and sustain competitive advantages. The so-called absorptive capacity consists of the company’s ability to acquire, assimilate, transform, exploit and use knowledge from the external environment for commercial purposes. By means of bibliometric techniques, the aim of this study is to analyze the academic production on absorptive capacity in the context of higher education institutions in order to map the gaps for new academic contributions in the area. 4231 papers were selected from Spell, Scielo, ScienceDirect, Ebsco, Scopus and Web of Science databases. After applying exclusion rules, 26 articles remained for analysis.